A visual interactive method for service prototyping. Issue 4 (8th July 2014) - Jung Bae, Dae; Seong Leem, Choon
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Despite the importance of the service design process, existing prototyping methods still have technical limitations, thus hampering the development of realistic service-experience simulations that can effectively reproduce service delivery situations and environments. In this study, a service-prototyping method based on 3D virtual reality (VR) technologies, the physical environment of a test bed, and related standard management procedures are described. In addition, a service-prototyping process for a servicescape is proposed based on a case study of an actual duty-free shop. The paper aims to discuss these issues. Design/methodology/approach – The study adopts a qualitative approach, using case studies to undertake a design and improvement plans for brand guidance structures for the brand observation convenience of customers in a duty-free shop. Findings – The findings of the study suggested environmental components and concept of 3D VR based test bed as an effective tool at the stage of service prototyping the core of new service development (NSD), and introduced practical methods for service prototyping in actual duty-free shop. The case study is significant due to the fact that it proved validity and practicality of the methods applied to service prototyping topic derivation and test process through target service analysis rather than optimal alternative selection. Practical implications – This study emphasizes the importance of prototyping during NSD and the value of the service prototyping test bed for practical use. It also proposes guidelines for the establishment and management of the test bed. Originality/value – In terms of service design research, this study also presented detailed operating procedures and methods through the new concept and in-depth case study of service prototyping using 3D VR technology.